Neutral Real Interest Rates in Inflation Targeting Emerging and Developing Economies - Ruch, Franz Ulrich (World Bank, Washington, DC, 2021)
With close to 30 emerging market and developing economies (EMDEs) using inflation targeting to determine monetary policy, and many of them for over 15 years, it is possible to create a meaningful measure of neutral real interest rates in these economies. The neutral real interest rate provides policymakers with a benchmark for the interest rate at which economic activity reaches its full potential and inflation will stabilize. The deviation of policy rates from this neutral rate determines whether monetary policy is accommodative or restrictive. This paper provides aggregate estimates of the neutral rate in 20 of these economies. EMDEs have seen a decline in the neutral rate of 4 percentage points, from over 6 percent in 2000 to closer to 2 percent at the end of 2019; advanced economies saw an above 2 percentage point decline over this period. The decline of neutral real interest rates in EMDEs can only partially be related to domestic drivers of desired savings and investment. The secular decline in the neutral rate of interest is limiting the ability of EMDEs to stimulate economies in the face of large shocks. The neutral real interest rate is unobservable and subject to a high degree of uncertainty, double the size of that for advanced economies. With such high uncertainty determining the stance of monetary policy in these economies is a challenge.